Expanding the scope of SiC ceramics through its surface modification by different methods; Surface and Coatings Technology; Vol. 435 - Feoktistov D. V. Dmitriy Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Sivkov A. A. Aleksandr Anatolyevich; Ivashutenko A. S. Alexander Sergeevich; Nikitin D. S. Dmitry Sergeevich; Shanenkov I. I. Ivan Igorevich; Abdelmagid A. M. H. Abdelrahman Mohamed Hamed; Orlova E. G. Evgeniya Georgievna (2022, 2022)
Title screen